2014
DOI: 10.1039/c4ra04493b
|View full text |Cite
|
Sign up to set email alerts
|

“The green side of the moon: ecofriendly aspects of organoselenium chemistry”

Abstract: Key aspects for the development of a greener synthesis and the use of the organoselenium compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(64 citation statements)
references
References 153 publications
0
64
0
Order By: Relevance
“…In this context, the procedure reported by Thomson et al . has been widely used in various organochalcogen transformation reactions as a source of Na 2 Se 2 . When freshly prepared 5‐alkyl‐2‐chloro‐1‐formyl‐3‐hydroxymethylenecyclohexenes {alkyl= H ( 22 ), Me ( 23 )}, were treated with in situ generated Na 2 Se 2 in presence of hexamethylphosphoramide (HMPA) in THF under reflux condition and the reaction time was extended from 7 h to 18 h, in addition to the expected 1,6‐dioxa‐6a‐selenapentalene, 11 and 1‐oxa‐6,6aλ 4 ‐diselenapentalene, 12 , a third product appeared as the prominent fraction (as monitored by thin layer chromatography).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the procedure reported by Thomson et al . has been widely used in various organochalcogen transformation reactions as a source of Na 2 Se 2 . When freshly prepared 5‐alkyl‐2‐chloro‐1‐formyl‐3‐hydroxymethylenecyclohexenes {alkyl= H ( 22 ), Me ( 23 )}, were treated with in situ generated Na 2 Se 2 in presence of hexamethylphosphoramide (HMPA) in THF under reflux condition and the reaction time was extended from 7 h to 18 h, in addition to the expected 1,6‐dioxa‐6a‐selenapentalene, 11 and 1‐oxa‐6,6aλ 4 ‐diselenapentalene, 12 , a third product appeared as the prominent fraction (as monitored by thin layer chromatography).…”
Section: Resultsmentioning
confidence: 99%
“…Given the continuous interest around the synthesis, the reactivity, and the biological properties of organochalcogen compounds and continuing our ongoing studies on the development of new ecofriendly protocols for the selenenylation of organic substrates, we investigated a new strategy for the preparation of selenoesters [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…These opened the way for a series of applications designed in order to address the principle of Green Chemistry, and a number of interesting results obtained during the last five years were recently collected in a review article [1].…”
Section: Water As An Alternative Medium For Organoselenium-catalyzed mentioning
confidence: 99%
“…Water is the natural medium for all biochemical reactions and is often claimed as an ideal green solvent [1,2] because it is non-toxic and non-flammable, has a high heat capacity in adsorbing the energy produced during a chemical reaction, and has low cost and large availability. Breslow [3], Sharpless [4], and several other authors [5] reported reactions that can be efficiently conducted "in-water" or "on-water" conditions.…”
Section: Introductionmentioning
confidence: 99%